2021
DOI: 10.2495/sc210471
|View full text |Cite
|
Sign up to set email alerts
|

Public Knowledge and Perception of Climate Change and Global Warming in the Context of Environmental Challenges and Policies in Saudi Arabia

Abstract: The adverse impacts of climate change have been experienced across the world including the Dammam City in Saudi Arabia. While there are many efforts targeted to fight climate change, their success is dependent on the public having sufficient knowledge about the issue. Hence, the fight against climate change urgently requires an increase in public awareness for effective mitigation measures. Thus, this study seeks to identify level of knowledge and awareness of the people of Dammam about climate changes, causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
6
3
1
Order By: Relevance
“…These results were based on similar studies conducted in other countries, which revealed that more than 80% of the respondents were aware of the problem of CC and its consequences ( 17 , 23 ). However, the research results contrast with studies conducted in Saudi Arabia, Turkey, and Kenya, which revealed a low level of knowledge about CC among participants ( 24 26 ). Notably, more than 75% of the participants were university graduates, with more than two-thirds of them having a field of study or occupation related to natural sciences, which have a significant association with high knowledge scores ( 27 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results were based on similar studies conducted in other countries, which revealed that more than 80% of the respondents were aware of the problem of CC and its consequences ( 17 , 23 ). However, the research results contrast with studies conducted in Saudi Arabia, Turkey, and Kenya, which revealed a low level of knowledge about CC among participants ( 24 26 ). Notably, more than 75% of the participants were university graduates, with more than two-thirds of them having a field of study or occupation related to natural sciences, which have a significant association with high knowledge scores ( 27 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Only 7% of the voters chose an act of God. These findings are consistent with the results of studies conducted in Egypt, Saudi Arabia, and Oman ( 24 , 30 , 31 ). However, in a study conducted in Ghana, more than one-third of the respondents stated that deforestation is the primary cause of CC; interestingly, a small percentages of participants referred to carbon emissions as the cause of CC, with nearly similar votes given to an act of God ( 23 ).…”
Section: Discussionsupporting
confidence: 92%
“…According to the researchers, it validated the implementation of the training program's efficacy and success. These results were marginally comparable to those of Almulhim A., (2021), who carried out research to determine the degree of knowledge of climate change, its causes, and its effects among residents of Dammam, Saudi Arabia. The study conducted by Almulhim et al (2021) revealed that a third of the participants exhibited an inadequate understanding of climate change.…”
Section: Discussionsupporting
confidence: 58%
“…This method was preferred since online surveys are quicker, more economical, and anonymous [51]. Snowball sampling method was used to distribute the survey link by email, where the participants shared the link with others in the area through email and WhatsApp groups [52][53][54]. The number of participants reached 810 at the end of three months.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The snowball sampling method allows studying a society anonymously when the response rate is high [54]. The online survey helped reach a maximum number of participants since distributing the survey to the public, especially female participants, would have been difficult [52,53].…”
Section: Data Collection and Analysismentioning
confidence: 99%